Sequence Variations of the Human MPDZ Gene and Association With Alcoholism in Subjects With European Ancestry - Karpyak, Victor M.; Kim, Jeong-Hyun; Biernacka, Joanna M.; Wieben, Eric D.; Mrazek, David A.; Black, John L.; Choi, Doo-Sup (Alcoholism, clinical and experimental research, 2009)
Background:  Mpdz gene variations are known contributors of acute alcohol withdrawal severity and seizures in mice. Methods:  To investigate the relevance of these findings for human alcoholism, we resequenced 46 exons, exon–intron boundaries, and 2 kilobases in the 5′ region of the human MPDZ gene in 61 subjects with a history of alcohol withdrawal seizures (AWS), 59 subjects with a history of alcohol withdrawal without AWS, and 64 Coriell samples from self‐reported nonalcoholic subjects [all European American (EA) ancestry] and compared with the Mpdz sequences of 3 mouse strains with different propensity to AWS. To explore potential associations of the human MPDZ gene with alcoholism and AWS, single SNP and haplotype analyses were performed using 13 common variants. Results:  Sixty‐seven new, mostly rare variants were discovered in the human MPDZ gene. Sequence comparison revealed that the human gene does not have variations identical to those comprising Mpdz gene haplotype associated with AWS in mice. We also found no significant association between MPDZ haplotypes and AWS in humans. However, a global test of haplotype association revealed a significant difference in haplotype frequencies between alcohol‐dependent subjects without AWS and Coriell controls (p = 0.015), suggesting a potential role of MPDZ in alcoholism and/or related phenotypes other than AWS. Haplotype‐specific tests for the most common haplotypes (frequency > 0.05), revealed a specific high‐risk haplotype (p = 0.006, maximum statistic p = 0.051), containing rs13297480G allele also found to be significantly more prevalent in alcoholics without AWS compared with nonalcoholic Coriell subjects (p = 0.019). Conclusions:  Sequencing of MPDZ gene in individuals with EA ancestry revealed no variations in the sites identical to those associated with AWS in mice. Exploratory haplotype and single SNP association analyses suggest a possible association between the MPDZ gene and alcohol dependence but not AWS. Further functional genomic analysis of MPDZ variants and investigation of their association with a broader array of alcoholism‐related phenotypes could reveal additional genetic markers of alcoholism.